Effect of the Peptidic Scaffold in Copper(II) Coordination and the Redox Properties of Short Histidine‐Containing Peptides. Issue 37 (28th July 2015) - Fragoso, Ana; Carvalho, Tiago; Rousselot‐Pailley, Pierre; Correia dos Santos, Margarida M.; Delgado, Rita; Iranzo, Olga
Abstract A linear decapeptide containing three His and one Asp residues and a β‐turn‐inducing dProPro unit was synthesised. A detailed potentiometric, mass spectrometric and spectroscopic study showed that at a 1:1 ratio of CCu/Cpeptide this peptide formed a major [CuH(OdProAsp)]2+ species (pH range 5.5–7.0), in which the Cu2+ ion was bound to the His and Asp residues in square‐planar or square‐pyramidal geometries. The stability constant corrected for protonated species (log K*<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgj2gd468ks" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> CuH(O dPro‐Asp)</alternatives>=9.33) is almost equal to the value obtained for the parent [CuH(OAsp)]2+ species (log K*CuH(O‐Asp)=9.28), but lower than that obtained for the cyclic [CuH(CAsp)]2+ complex (log K*CuH(C‐Asp)=10.79) previously published. Thus, the replacement of the ProGly unit by the stronger β‐turn‐inducing dProPro unit did not generate a more stable copper(II) species, although the OdProAsp peptide was structured in solution, as shown by circular dichroism (CD) spectroscopy. Interestingly, the calculated value of Keff showed that this peptide behaved similarly to the OAsp or CAsp counterparts, depending on the pH value. The cyclic voltammetry data indicated that the most easily reducible species were [CuH(OAsp)]2+ (E′0=262 mV versus a normal hydrogen electrode (NHE)) and [CuH(OdProAsp)]2+ (E′0=294 mV versus NHE) complexes, the peptidic scaffolds of which are open. A lower value was obtained for [CuH(CAsp)]2+ (E′0=24 mV versus NHE). A different degree of non‐reversibility was observed for the three copper(II) complexes; this could reflect a different degree of flexibility in their respective peptidic scaffolds.